Pendidikan Media Digital untuk Mencegah Dampak Negatif Game Online Terhadap Nilai Kebangsaan - Wanda Sri Wahyuni; Dan Riadi Pratama; Saepul Dahyar; Muhammad Jahran Rivaldi; Herli Antoni (Institut Nalanda, 2025)
Digital media education is one of the important solutions in dealing with the negative impact of online games on national values among the younger generation. The background of this research departs from concerns about the influence of online games that contain violence, individualism, and lack of respect for cultural plurality, which can be contrary to Indonesian national values. The purpose of this research is to explore the role of digital media education in preventing these negative impacts and introducing national values through online games. The method used in this study is a qualitative approach with in-depth interview techniques, observation, case studies, and focus group discussions. The results of the study show that online games can have a positive or negative impact, depending on the type of game played. Games that contain elements of violence and extreme competition tend to erode national values, while educational games with historical and cultural themes can reinforce national values. Digital media education based on national values has proven to be effective in helping students choose games that educate and introduce Pancasila values. In conclusion, the application of digital media education that is integrated with national values needs to be expanded throughout Indonesia, by involving educators, parents, and the government to create a young generation that is smart in using technology and maintaining national values.